Pengaruh Model Discovery Learning pada Materi APBN dan APBD Terhadap Hasil Belajar Siswa Kelas XI IPS di SMA Negeri 2 Bandar - Yessy Sinaga; Susy Alestriani Sibagariang; Debbi Petra Meyana Sitorus (Departement of Mathematics Education, 2023)
This study aims to determine the effect of using the discovery learning model on student learning outcomes in class XI IPS at SMA Negeri 2 Bandar. The type of research used in this research is quantitative research. The quantitative research method is a type of research whose specifications are systematic, planned and clearly structured from the start to the creation of the research design. This research will be carried out at SMA Negeri 2 Bandar starting from April 2022 – May 2023. The population in this study are all students of class XI IPS SMA Negeri 2 Bandar for the academic year 2022/2023 which consists of 4 classes with a total of 128 students. person. In this study, there was one class as the experimental class and one as the control class. This data collection technique must be in accordance with the instrument used by the author in obtaining data, therefore the technique used by the author is observation and testing. Based on the results of the study, it was concluded that the discovery learning model on APBN and APBD material with the T-Test Hypothesis obtained a sig (2-tailed) value of 0.003 <0.05, so there is a significant influence. The results of the analysis of the paired sample test show that t count > t table where t count is 4,360 and t table is 4,358.